Innovation and Education: lessons learned from Cuban Science, Technology and Innovation System - Armando Rodríguez Batista (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología, 2022)
The beginning of Science and Technology-Based Innovation (STI) policies in Cuba should be traced to 1961, with the so-called Literacy Campaign that declared the Nation as the First Latin-American Country Free from Illiteracy. From this moment to our days, Cuba has developed a significant Research and Development (R&D) infrastructure and committed human resources on Science, Technology and Innovation.